The Reliability Analysis for Corporative IP-Telephony System with Functional Safety - A. E. Alexandrovich; V. O. Chuckanov; I. M. Yadykin (Безопасность информационных технологий, 2011)
The article is devoted to issues of reliability modeling for fault tolerant corporative IP-telephony system. Two reliability models are presented based on the minimal paths and minimal cuts technique. Two reliability models are proposed based on the link connection concept. IP-telephony corporative system fault tolerance research is conducted with the aid of proposed reliability models.